Penerapan Psikologi Kognitif Dalam Mengolah Berita Hoax Di Media Sosial Selama Pandemi Covid-19 Di Kampung Santren Surabaya - Sofia Zaini Kulbi (Fakulatas Dakwah IAIN Salatiga, 2020)
Abstract Hoax news is considered to be an important problem faced by society today. Along with the covid-19 pandemic, it is possible for someone who is not responsible to misuse social media to spread hoax news about the Covid-19 pandemic for personal benefit. So, the understanding and processing information on social media requires cognitive abilities that each individual must have. This paper will discuss cognitive psychology, covid-19, and the characteristics and types of hoax news. Then the analysis of this paper is to describe how the application of cognitive thinking in processing hoax news during the covid-19 pandemic. The results of this analysis are that people do not get caught up in hoax news, there are 3 stages of cognitive thinking in processing hoax news during the Covid-19 pandemic, the first is the conceptual framework of thinking in seeing news, thesecond is thinking logically and critically in analyzing news, and third is makingdecisions on a news. AbstrakBerita hoax dinilai menjadi problematika penting yang sedang dihadapi masyarakat di zaman sekarang. Bersamaan dengan adanya pandemi covid-19, tidak menutup kemungkinan bagi seseorang yang tidak bertanggung jawab untuk menyalahgunakan media sosial guna menebar berita hoax tentang pandemi covid-19 demi keuntungan pribadi. Maka, dalam memahami dan mengolah informasi di media sosial diperlukan cognitive abilities (kemampuan kognitif) yang harus dimiliki oleh setiap individu. Dalam tulisan ini akan diulas mengenai psikologi kognitif, covid-19, serta ciri-ciri dan jenis berita hoax. Kemudian analisis dari tulisan ini adalah menjabarkan bagaimana penerapan pemikiran kognitif dalam mengolah berita hoax selama pandemi covid-19.Hasil dari analisis tersebut adalah agar masyarakat tidak terjebak ke dalam berita hoax, terdapat 3 tahapan pemikiran kognitif dalam mengolah berita hoax selama pandemi covid-19, yang pertama adalah kerangka konsep berpikir dalam melihat sebuah berita, kedua adalah berpikir logis dan kritis dalam menelaah sebuah berita dan ketiga adalah mengambil keputusan atas sebuah berita.